2008
DOI: 10.3858/emm.2008.40.5.574
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitor KBH-A42 inhibits cytokine production in RAW 264.7 macrophage cells and in vivo endotoxemia model

Abstract: In light of the anti-inflammatory properties of histone deacetylase (HDAC) inhibitors, such as suberoylanilide hydroxamic acid (SAHA) and trichostatin A (TSA), we examined a new HDAC inhibitor KBH-A42 for its anti-inflammatory activities. KBH-A42 showed noteworthy anti-inflammatory properties in vitro via suppression of the production of TNF-α, a proinflammatory cytokine, and nitric oxide (NO), a proinflammatory effector molecule, in LPS-stimulated RAW264.7 cells and peritoneal macrophages. It also inhibited T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 23 publications
2
48
1
Order By: Relevance
“…The available studies on epigenetic modifiers in several animal models have shown different results; i.e. effects of epigenetic modifiers varied from having no effect to being beneficial in attenuating inflammatory cytokines and chemokines as well as inflammatory injury to the airway, digestive tract and joints (Choi et al, 2008;Iwata et al, 2002;Rahman, 2002;Zhang et al, 2010). The variability in results might be because previous studies have focused on effects pre-treatment with HDAC inhibitors has, rather than studying their therapeutic potential.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The available studies on epigenetic modifiers in several animal models have shown different results; i.e. effects of epigenetic modifiers varied from having no effect to being beneficial in attenuating inflammatory cytokines and chemokines as well as inflammatory injury to the airway, digestive tract and joints (Choi et al, 2008;Iwata et al, 2002;Rahman, 2002;Zhang et al, 2010). The variability in results might be because previous studies have focused on effects pre-treatment with HDAC inhibitors has, rather than studying their therapeutic potential.…”
Section: Discussionmentioning
confidence: 60%
“…A more recent KBH-A42 HDAC inhibitor has been recognized as an anti-inflammatory drug through its capability of reducing the production of TNFα and nitric oxide in LPS-induced macrophages. This study has also shown that the substantial antiinflammatory response of KBH-A42 is mediated through the phosphorylation of p38MAPK, but not through the activation of ERK1/2 or JNK (Choi et al, 2008).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Trichostatin A has been shown to enhance the LPS-induced expression of Cox-2, Cxcl2, and Lfit2 in bone marrow-derived macrophages (Aung et al, 2006). A new HDAC inhibitor KBH-A42 showed antiinflammatory properties in vitro via suppression of the production of TNFa and nitric oxide (NO) by dose-dependent increase in DNA binding with AP-1 and decrease in p38 phosphorylation in macrophages (Choi et al, 2008). In the present study, we found that knockdown of expression of miR-146a restored the levels of IL-6 in TSA ⁄ LPS-treated cells in macrophages from aged mice, suggesting that TSA diminishes the production of IL-6 in LPS-treated macrophages from aged mice by up-regulating miR-146a expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The HDAC inhibitors were reported to promote apoptosis as well as modulation of the expression of various proinflammatory cytokines (49). Cytokine inhibition equally shown for the HDAC inhibitor KBH-A42 in RAW 264.7 cells is paralleled by a suppressed MAP kinase phosphorylation (50).…”
Section: Dendritic Cells and Macrophagesmentioning
confidence: 99%